Associations of polyunsaturated fatty acids and genetic predisposition with cardiovascular risk among hypertensive adults - Li, Jindi; Zhang, Yubo; Liu, Shaohui; Nong, Cuihua; Chen, Quanhong; Zou, Yunfeng; Peng, Yang; Chen, Hao (Frontiers in Nutrition, 2025)
BackgroundHypertension is linked to elevated cardiovascular morbidity and mortality. Research findings regarding cardiovascular benefits of polyunsaturated fatty acids (PUFAs) are inconsistent, possibly due to unbalanced N6FA/N3FA (omega-6 to omega-3 polyunsaturated fatty) ratios and genetic predispositions in PUFAs utilization and cardiovascular disease (CVD) risk. This study investigates the association between plasma PUFAs and CVD risk among hypertensive adults, stratified by the polygenic risk score (PRS) for PUFAs and CVD.MethodsThe study analyzed 135,969 hypertensive adults from the UK Biobank. Cox regression models were employed to assess the links between PUFAs and cardiovascular outcomes, as well as the moderating effect of PRS.ResultsDuring the follow-up, 22,084 (16.2%) of participants experienced CVD events, and 2,336 (1.7%) and 13,823 (10.2%) died from CVD and all causes, respectively. Higher blood levels of total polyunsaturated fatty acids (Total PUFA), N3FA, N6FA, docosahexaenoic acid (DHA), and linoleic acid (LA) were associated with lower CVD incidence and mortality, for instance, the hazard ratio for N3FA was 0.745 [95% confidence interval (0.698, 0.796)]. Furthermore, the N6FA/N3FA ratio showed a positive association with CVD incidence and mortality, with the point of minimum risk estimated at approximately 8.70 based on restricted cubic spline analysis. Protective associations of Total PUFA, N6FA, and LA with CVD incidence were stronger in individuals with lower CVD – PRS scores.ConclusionDespite the general cardiovascular benefits of PUFAs, a higher N6FA/N3FA ratio was associated with an elevated risk of CVD in hypertensive participants. The benefits of PUFAs are greater in those with lower genetic CVD risk. This emphasizes the need to consider N6FA/N3FA balance and genetic predisposition when assessing health impact of PUFAs on CVD.